Innovation in public policy : evaluating the case studies from Rio Grande do Sul - Tonetto, Jorge Lu?s (2024)
This thesis comprises three essays that relate to tax innovations that occurred in Rio Grande do Sul State from 2019 to 2022. The State's main revenue is an indirect tax on consumption, which has the characteristics of regressivity and fiscal anesthesia. The innovations presented and evaluated in this thesis comprise solutions for these issues. Thus, in the first essay we present a study that aims to verify the impact of the COVID-19 pandemic on the use of the Menor Pre?o Brasil app service. To this end, it investigates both the correlation between confirmed cases of COVID-19 in Brazil and the changes in the application?s functionalities with the variation in citizens? queries to the application. For this purpose, the method of identifying multiple structural breaks and regression models are employed. The results indicate that a 1% increase in COVID-19 cases led to a 0.2% increase in queries. The results confirm also that user behavior related to application was influenced by the change in the app?s feature and by inflation rates. In the second essay, we study the program (the Devolve-ICMS Program) that refunds consumption tax to low-income citizens (cashback). This study aims to evaluate the impacts of this Program using a differences-in-differences model and having, as response variables, the monthly sum of electronic invoices issued to the Program?s beneficiaries, as well as their value.The results show that the Program is effective, as it has reduced tax pressure on poor people and increased both the number of invoices issued and their value. Finally, the last essay is about the use of monetary incentives through Receita Certa project. Targeted at the commerce sector, this initiative offers cashback rewards, refunding a portion of the consumption tax to citizens. This study evaluates the impacts of Receita Certa using a difference-in-differences model. The response variables are the monthly number and value of electronic invoices issued to beneficiaries. Refunds are contingent on certain conditions, such as revenue exceeding inflation. The results show that the Receita Certa is ineffective, as it decreased the number of tax documents issued and it is not significant about variable value of the documents. Additionally, the initiative?s cost was high, highlighting the need for reevaluation and refinement. States that have a large tax gap need to improve their control systems. Initiatives such as those presented in this thesis seek to engage taxpayers in combating evasion, some more successfully than others. The objective of these studies was to contribute to better public policies in tax administration.